Colombia : First Review Under the Stand-By Arrangement, Requests for Modification of Performance Criteria, and Waiver of Nonobservance of Performance Criteria and of Applicability of end-September Performance Criteria. (IMF Staff Country Reports; Country Report, 2005)
This paper discusses key findings of the First Review Under the Stand-By Arrangement for Colombia. The economy is expected to continue to perform well in 2005. Real GDP is expected to grow by 4 percent, with consumer prices rising by 5 percent, as targeted. The external current account deficit is estimated at 1 percent of GDP, compared with 2.8 percent of GDP projected originally. Economic performance under the arrangement has been favorable. IMF staff supports the authorities' request for completion of the first review, for modification of the fiscal targets, and for waivers.